Prospective Study of (68)Ga-DOTATATE Positron Emission Tomography/Computed Tomography for Detecting Gastro-Entero-Pancreatic Neuroendocrine Tumors and Unknown Primary Sites - Sadowski, Samira M. (J Clin Oncol, 2016)
PURPOSE: Gastro-entero-pancreatic neuroendocrine tumors (GEPNETs) are increasing in incidence, and accurate staging is important for selecting the appropriate treatment. (68)Ga-DOTATATE imaging is a promising approach for detecting GEPNETs and could help in selecting optimal therapeutic strategies. The aim of this study was to prospectively determine the clinical utility of (68)Ga-DOTATATE positron emission tomography (PET)/computed tomography (CT) in detecting unknown primary and metastatic GEPNETs. PATIENTS AND METHODS: One hundred thirty-one patients were enrolled in a prospective study of patients undergoing (68)Ga-DOTATATE PET/CT, (111)In-pentetreotide single-photon emission computed tomography (SPECT)/CT and multiphasic CT scan, and/or magnetic resonance imaging in a blinded fashion with comprehensive biochemical testing. The primary outcome measure was the detection of lesions by each imaging study. RESULTS: (68)Ga-DOTATATE PET/CT imaging detected 95.1% of lesions (95% CI, 92.4% to 96.8%) with an average maximum standardized uptake value of 65.4 ± 47 (range, 6.9 to 244), anatomic imaging detected 45.3% of lesions (95% CI, 37.9% to 52.9%), and (111)In-pentetreotide SPECT/CT detected 30.9% of lesions (95% CI, 25.0% to 37.5%), with a significant difference between imaging modalities (P < .001). In four of 14 patients (28.6%), (68)Ga-DOTATATE PET/CT found a previously unknown primary tumor, and detected primary GEPNET, lymph node, and distant metastases correctly in 72 of 113 lesions (63.7%) when compared with histopathology, with 22.1% and 38.9% detected by using (111)In-pentetreotide SPECT/CT and anatomic imaging, respectively. On the basis of findings with (68)Ga-DOTATATE PET/CT, 43 of 131 patients (32.8%) had a change in management recommendation. In patients with carcinoid symptoms but negative biochemical testing, (68)Ga-DOTATATE PET/CT detected lesions in 65.2% of patients, 40% of which were detected neither by anatomic imaging nor by (111)In-pentetreotide SPECT/CT. CONCLUSION: (68)Ga-DOTATATE PET/CT imaging provides important information for accurate staging of GEPNETs and selection of appropriate treatment interventions even in the absence of biochemical evidence of disease in symptomatic patients.